Isolation and Characterisation of Beta-sitosterol from the rhizomes of Arisaema utile and its Evaluation for Antioxidant Activity - Bhat, Arif Hussain; Alia, Aparna; Rather, Ghulam Mustafa; Kumar, Bharty (International Journal of Scientific Research in Biological Sciences, 2019)
The aim of this study is isolation, identification and characterized the bioactive compounds from the rhizomes of arisaema utile. Preliminary Phytochemical screening of the rhizome extract of arisaema utile revealed the presence of Steroids, terpenoids, Flavonoids, Alkaloids, Saponins & Carbohydrates. The air dried rhizomes were pulverized to powder, subjected to Soxhlet extraction and compound Isolation. The isolated compound was colorless crystalline, which was further subjected to IR, 13CNMR and 1HNMR for proper characterization and elucidation of the structure. The compound was concluded as β-Sitosterol. Antioxidant activity of the isolated compound was measured by DPPH assay under in-vitro condition. The isolated compound showed most promising radical scavenging activity at concentration of 10μg/ml.